2001
DOI: 10.1088/0268-1242/16/10/304
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic analysis of the MBE growth of GaInAsN

Abstract: A thermodynamic approach to analysis of the growth of InGaAsN compounds by molecular beam epitaxy (MBE) is proposed. The developed thermodynamic model allows estimation of the mole fraction of nitrogen in the obtained alloys as a function of external growth parameters: element fluxes and growth temperature. The model predicts that the nitrogen incorporation is temperature-independent below 500 • C and markedly diminishes at higher growth temperatures. The incorporation of nitrogen is suppressed on raising the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
15
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 14 publications
7
15
0
Order By: Relevance
“…This rise in PL intensity is accompanied by an increase in PL wavelength. Xray diffraction on ternary reference samples reveals an increased N-incorporation which has also been reported by other authors [6,7] and is a clear indication that under higher As fluxes the N incorporation is limited by the competition between the group V elements. The same increase in the N content of InGaAsN quantitatively explains the redshift in PL wavelength.…”
Section: Growthsupporting
confidence: 86%
“…This rise in PL intensity is accompanied by an increase in PL wavelength. Xray diffraction on ternary reference samples reveals an increased N-incorporation which has also been reported by other authors [6,7] and is a clear indication that under higher As fluxes the N incorporation is limited by the competition between the group V elements. The same increase in the N content of InGaAsN quantitatively explains the redshift in PL wavelength.…”
Section: Growthsupporting
confidence: 86%
“…The temperature-independent behavior of the nitrogen incorporation coincides with previous observations on InGaAsN and GaAsN [11]. A thermodynamic study for MBE grown GaAsN and InGaAsN showed that the unchanged nitrogen composition below 480 1C can be attributed to a near-unity sticking coefficient for nitrogen adatoms.…”
Section: Resultssupporting
confidence: 88%
“…In agreement with the other published data and the predictions of our thermodynamic calculations [9] we have found that the sticking 2.0 coefficient of nitrogen is temperature independent RHEED over the range of 400-530'C and decreases at 2x4 higher temperatures. Therefore, we used the same E 1,613 characteristics of RF plasma source in this temperature interval to have equal nitrogen content • / for GaAsN provided the growth rate was fixed.…”
Section: Effect Of Growth Temperature and Growth Ratesupporting
confidence: 93%